Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.5194/npg-15-615-2008
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric multifractal model for solar wind intermittent turbulence

Abstract: Abstract. We consider nonuniform energy transfer rate for solar wind turbulence depending on the solar cycle activity. To achieve this purpose we determine the generalized dimensions and singularity spectra for the experimental data of the solar wind measured in situ by Advanced Composition Explorer spacecraft during solar maximum (2001) and minimum (2006) at 1 AU. By determining the asymmetric singularity spectra we confirm the multifractal nature of different states of the solar wind. Moreover, for explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…It can be observed that the model fits the data well. The values estimated for multifractality and symmetry are slightly different from those obtained by Szczepaniak and Macek (2008). The discrepancy is primarily due to the differences in the fractal dimensions at the right end of the spectra.…”
Section: Example 2: Szczepaniak and Macek's Solar Wind Datamentioning
confidence: 45%
See 2 more Smart Citations
“…It can be observed that the model fits the data well. The values estimated for multifractality and symmetry are slightly different from those obtained by Szczepaniak and Macek (2008). The discrepancy is primarily due to the differences in the fractal dimensions at the right end of the spectra.…”
Section: Example 2: Szczepaniak and Macek's Solar Wind Datamentioning
confidence: 45%
“…The discrepancy is primarily due to the differences in the fractal dimensions at the right end of the spectra. It is noteworthy that the model that Szczepaniak and Macek (2008) used to fit the data with the curve reaches zero at both ends, whereas the curve fitted by the new model reaches zero only at one end but not at the other end. The results also indicate that the distribution has strong multifractality and a left-skewed asymmetry.…”
Section: Example 2: Szczepaniak and Macek's Solar Wind Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, to study turbulence cascade Macek and Szczepaniak (2008) have selected four-day time intervals of v x samples in 1976 (solar minimum) for both slow and fast solar wind streams measured by Helios 2 at various distances from the Sun. The results for ACE data at 1 AU and dependence on solar cycle are discussed by Szczepaniak and Macek (2008). We have analysed time series of velocities of the solar wind measured by Voyager 2 at various distances from the Sun, 2.5, 25, and 50 AU, selecting longer (13-day) 1978-1988-1997(Macek and Wawrzaszek, 2009.…”
Section: Solar Wind Datamentioning
confidence: 99%
“…In particular, the multifractal spectrum has been investigated using Voyager (magnetic field fluctuations) data in the outer heliosphere (Burlaga, 1991(Burlaga, , 2001) and using Helios (plasma) data in the inner heliosphere (Marsch et al, 1996). The multifractal scaling has also been investigated using Ulysses observations, e.g., (Horbury and Balogh, 2001; and with Advanced Composition Explorer (ACE) and WIND data, e.g., (Hnat et al, 2003;Szczepaniak and Macek, 2008).…”
Section: Introductionmentioning
confidence: 99%